CHAT GPT PARA FOMENTAR EL APRENDIZAJE AUTONOMO DE LOS ESTUDIANTES DE LA CARRERA DE PEDAGOGIA DE LAS CIENCIAS EXPERIMENTALES INFORMATICA DE LA UNIVERSIDAD TECNICA DE BABAHOYO, PERIODO ACADEMICO OCTUBRE 2023- MARZO 2024 - DAVILA PINEDA CHANOA GRISELDA (2024)
The GPT Chat is an artificial intelligence that has been very helpful for the student to independently acquire their knowledge, allowing us to generate information quickly and efficiently. The objective of this research is to determine the influence of the GPT Chat to promote autonomous learning of students of the experimental computer science pedagogy career at the Technical University of Babahoyo, academic period October 2023-March 2024. It was required to apply the methodologies descriptive and exploratory with the purpose of collecting and searching for information from different reliable sources through the quantitative approach with the implementation of 10 closed questions for the students, the data collection technique was the survey and the instrument where we carried out the work was Google Forms, the responses were based on the Likert scale with a sample of 170 students. With the execution of the surveys, it was possible to conclude that the influence of the GPT Chat was determined to promote the autonomous learning of the students of the pedagogy career of experimental computer sciences at the technical university of Babahoyo, academic period October 2023 - March 2024.